The effect of type 2 diabetes mellitus on early postoperative cognitive functions - Seven, Seda; Ceylan, İlkay and Kaymak, Durmuş and Kara, Ali Giray and Erden, Veysel (Journal of Surgery and Medicine, 2022)
Background/Aim: Postoperative cognitive dysfunction (POCD) is an important problem that is encountered perioperatively and has a complex pathophysiology. Diabetes mellitus (DM) can cause adverse effects on cognitive functions, such as memory dysfunctions, psychomotor retardation, slower information processing, impairment of complex motor functions, deterioration of verbal rationality, and attention deficit. We assume that DM will have a triggering effect on POCD. Mild cognitive dysfunction caused by diabetes mellitus may increase the risk of POCD. For this purpose, we aimed to investigate the effect of type 2 DM on early POCD. Methods: Fifty literate patients who ranked 1-2 on the American Society of Anesthesiologists (ASA) scale were included in our prospective case-control study. They ranged in age from 35 to 70. All were scheduled for elective laparoscopic cholecystectomy at the İstanbul Training and Research Hospital. Patients were divided into two groups: the diabetes mellitus group and the control group. The DM group consisted of 25 patients who had been diagnosed with type 2 DM and had been on regular oral antidiabetic medication or insulin for at least five years. To examine the patients neuropsychologically, the Mini Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA) Test were conducted one day before the surgery. The MMSE and MoCA were repeated at the 4th and 24th hours postoperatively. The patients were monitored to record their depth of anesthesia, peak heart rate, mean arterial pressure, oxygen saturation, end-tidal carbon dioxide value, and expiratory sevoflurane concentration prior to perioperative intubation and every five minutes after intubation until the end of the operation. The state of postoperative pain and total analgesic dose used for the patients were also recorded. Results: Demographic data in both groups were similar in terms of age, gender, body mass index, and duration of surgery (P > 0.05 for each). Perioperative depth of anesthesia, hemodynamic data, and postoperative pain scores were similar in both groups (P > 0.05 for each). While there was initially no significant difference between the groups in terms of preoperative cognitive function, compared with the control group, the DM group had significantly lower values of MMSE and MoCA at the postoperative 4th (P = 0.014 and P = 0.014) and 24th hour (P = 0.026 and P = 0.01) . Conclusion: Our study shows that the early postoperative cognitive functions of diabetic patients are affected more than non-diabetic patients in laparoscopic surgery. MMSE and MoCA tests are appropriate for screening type 2 diabetic patients. Thus, complications can be prevented in diabetic surgical patients by detecting cognitive dysfunction in the early stages, so that appropriate treatment can be initiated.